E-WASTE from TECHNOLOGY USE in the OIL and GAS SECTOR: The SNEAK PEEK - Nordin, M. (Little Lion Scientific, 2021)
Electronic Waste (E-Waste) generation has been escalating since the past decade. Soundly managing this particular type of waste is one of the methods in creating a more sustainable world for the future. The terms digitization, digitalization, and digital transformation are spurring across all the industries vertically and horizontally. In aligning the business strategy and information technology strategy, cooperation from various industries is investing in the latest and advanced technologies to stay forefront with the movement of Industry 4.0. This reflects the input which is one end of the product value chain. Meanwhile, another end of the product value chain is the output. The output is signified by the amount of E-Waste generated, once Electrical & Electronics (E&E) equipment and Internet-Of-Things (IoT) hardware, electronic circuits, and sensors reached the End-of-Life (EOL). This paper will provide a sneak peek into how much E-Waste is highlighted in the oil and gas industry. It is a part of research that studies the management of E-Waste in the oil and gas industry. Design Thinking is introduced into the methodology that is implemented simultaneously with the single case study approach. The research model is based on the DPSIR Model, which stands for Driver-Pressure-State-Impact-Response Model. Â© 2021 Little Lion Scientific